Penerapan Standar Pelayanan Kefarmasian di Apotek Kimia Farma Kecamatan Banjarsari - Syifa Febiana; Risma Sakti Pambudi; Khotimatul Khusna (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2023)
The application of pharmaceutical service standards in Indonesian pharmacies has not been fully implemented, often referred to as services that do not comply with statutory provisions, where pharmacies are like shops that only sell drugs. This study aims to determine the application of pharmaceutical service standards at the Kimia Farma pharmacy in Banjarsari District. The method used is descriptive method using a cross-sectional research design. The research samples were the Kimia Farma Kadipiro pharmacy and the Kimia Farma Yosodipuro pharmacy. The research instrument used a questionnaire which was tested for validity and reliability tests using SPSS 21. The results showed that the application of pharmaceutical service standards at the Kimia Farma Kadipiro pharmacy was 86% and at the Kimia Farma Yosodipuro pharmacy was 80%. The conclusion of this study is that the application of pharmaceutical service standards at the Kimia Farma Kadipiro pharmacy shows very suitable criteria and the Kimia Farma Yosodipuro pharmacy shows appropriate criteria according to the Regulation of the Minister of Health of the Republic of Indonesia Number 73 of 2016.